PELATIHAN PERBAIKAN AC MOBIL BAGI KARANG TARUNA PANJI PUSPA DI DESA GUMPANG KECAMATAN KARTASURA MENUJU USAHA MANDIRI - Arif Surono; Sudiro Sudiro; Wachid Yahya; Onery Andi Saputra; Sunaryo Sunaryo (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
This paper reports on community service activities carried out by the Politechnic Indonusa of Surakarta team foreign exchange reserves. Devotion is focused on the members of the cadet reef who have graduated from school that aim to provide knowledge and skill regarding repairs and maintenance of air conditioning (ac) cars. Through this program, it is expected that participants will be better prepared to open jobs in the service areas. This devotion begins with theoretical delivery, consisting of basic component materials and an automobile - conditioned mechanical system. Materials are delivered by methods of speech, discussion and question-and-answer. Participants are given understanding on how the components work, unloading the tides, checking damage, cleaning and trouble shooting on car ac units. The training was followed by 22 participants. The results of this training, being able to provide skill and understanding in the repair of car air conditioning, make it possible for participants to start their own businesses especially in the proper and proper areas of care and car ac repair.